Blowup for Systems of Semilinear Wave Equations with Small Initial Data (Journal of Partial Differential Equations, 2004)
This paper deals with the Cauchy problem for the system of semilinear wave equations with small initial data. We give the upper bounds for the lifespan of the classical solution to the systems.
Keywords: Wave equations; classical solution; blow up; lifespan